DESCRIPTION OF THE SYMPTOMS OF HYPERTENSION CHARACTERISTICS CONFIRMED BY COVID-19 AT THE INPATIENT INSTALLATION OF PANEMBAHAN HOSPITAL, YOGYAKARTA IN 2020 - Fitri Andriani Fatimah; Anis Febri Nilansari; Rahmad A Hi Wahid (UNEJ e-Proceeding, 2022)
Background: The trend of hypertension is increasing every year. It is estimated that 1.13 billion people worldwide have hypertension 2/3 of low-middle income countries. Hypertension is the highest comorbid group in COVID-19 patients, which is 50.5%. This causes an increased risk of dangerous infections that can lead to death. The fact that the SARS-Cov-2 virus uses the Angiotensin Converting Enzym-2 receptor as an entry point to colonize in the body can cause vasoconstriction and inflammation that can worsen the incidence of hypertension and cardiovascular disease. Purpose: This study aims to determine the characteristics of hypertensive patients with confirmed COVID-19 in the inpatient installation of Panembahan Hospital, Senopati, Bantul in 2020. Methods: This study is a descriptive observational study using secondary data in the form of medical records conducted at Panembahan Hospital, Senopati, Bantul. A total of 21 medical record samples were taken that met the inclusion criteria. Samples were taken from December to October 2020 using the total sampling technique. Results: The results of data analysis using the SPSS program obtained a total of 21 samples that met the criteria. There were 10 male patients (47.6%), female 11 patients (52.4%), age >54 years totaling 15 patients (71.4%). The dominant symptoms felt were cough, fever, headache, shortness of breath, malaise, abdominal pain and sore throat totaling 19 patients (90.4%). Conclusion: COVID-19 disease with the most comorbidities is Hypertension, Hypertension with Diabetes Mellitus, followed by Hypertension with Chronic Kidney Failure. The therapy patterns that are often used in Panembahan Hospital, Senopati, Bantul for hypertension patients with Covid-19 are Calcium Channel Blocker (Amlodipine), Angiotensin Receptor Blocker (Valsartan and Candesartan), and Loop Diuretics (Furosemide and Spironolactone).